2019
DOI: 10.1111/joor.12886
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular disorders, pain in the neck and shoulder area, and headache among musicians

Abstract: Background Uncertainties still exist about the role of playing musical instruments on the report of musculoskeletal complaints and headache. Objectives To evaluate the prevalence of and risk indicators for symptoms of temporomandibular disorders, pain in the neck or shoulder, and headache among musicians. Methods A questionnaire was distributed among 50 Dutch music ensembles. Results The questionnaire was completed by 1470 musicians (response rate 77.0%). Of these, 371 musicians were categorised as woodwind pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 38 publications
2
44
0
5
Order By: Relevance
“…Of the 13 selected studies, three were conducted in Portugal, 6,19,21 two were carried out in Brazil, 23,27 and the remaining eight were conducted in Spain, 24 Korea, 20 Japan, 22 Poland, 26 Germany, 25 Holland, 28 Nigeria 29 and Chile 30 . Regarding the type of study, only one dissertation 19 and one course conclusion paper 30 were selected; the others were articles published in peer‐reviewed Journals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 13 selected studies, three were conducted in Portugal, 6,19,21 two were carried out in Brazil, 23,27 and the remaining eight were conducted in Spain, 24 Korea, 20 Japan, 22 Poland, 26 Germany, 25 Holland, 28 Nigeria 29 and Chile 30 . Regarding the type of study, only one dissertation 19 and one course conclusion paper 30 were selected; the others were articles published in peer‐reviewed Journals.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size ranged from 31 25 to 1470 28 participants. Four articles 21,27,28,31 used the RDC/TMD diagnostic tool.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study with these individuals, using the same diagnostic method, found a prevalence of 68.3% of participants with some type of TMD 15 . A research that investigated the association between being a musician and having shoulder, neck and head pain, or having TMD symptoms, found results that support the association between the presence of TMD and the practice of woodwind instruments 16 . When comparing the prevalence obtained in this study with prevalence in other risk groups, such as high impact athletes, a study with professional of mixed martial arts showed that 61% of them had some type of TMD, while the prevalence among athletes of the Brazilian karate team was 54% 17 .…”
Section: Discussionmentioning
confidence: 95%